2019
DOI: 10.1021/acsami.9b14704
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of CuO with Bi2MoO6 Nanosheets as a Surface Multifunctional Photocatalyst for Toluene Oxidation under Solar Irradiation

Abstract: Herein, CuO/Bi 2 MoO 6 hybrid nanosheets were prepared as a surface multifunctional photocatalyst for gas-phase toluene oxidation with high conversion (>99%). Aberration-corrected scanning transmission electron microscopy suggested that CuO species were highly dispersed on the nanosheets. X-ray absorption fine structure spectra indicated that the distorted and stretched Cu−O coordination structures in CuO/Bi 2 MoO 6 nanosheets would provide open active sites. In situ Fourier transform infrared and density func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…As shown in Figure S9b, Supporting Information, the characteristic bands of toluene (≈3027 cm −1 ) assigned to the aromatic ring of CH bond vibration were gradually reduced with prolonging irradiation time, while the broad peak located at ≈1683 cm −1 corresponding to the carbonyl group of benzaldehyde emerged and slightly increased. [ 38,39 ] These results indicated that the toluene molecules absorbed on the surface of catalyst reacted rapidly with holes and ·O 2 − under light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S9b, Supporting Information, the characteristic bands of toluene (≈3027 cm −1 ) assigned to the aromatic ring of CH bond vibration were gradually reduced with prolonging irradiation time, while the broad peak located at ≈1683 cm −1 corresponding to the carbonyl group of benzaldehyde emerged and slightly increased. [ 38,39 ] These results indicated that the toluene molecules absorbed on the surface of catalyst reacted rapidly with holes and ·O 2 − under light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…This confirmed the photocatalytic activity effect of CeO 2 semiconductor oxide with tuneable NRs morphology for the oxidation of pinene to oxygenated compounds. The obtained photocatalytic activity of CeO 2 nanostructures for oxyfunctionalization of the pinene inert CÀ H bond is comparable to the other multicomponents catalysts such as Zn 2 Tilayered double hydroxide, [44] heterojunction CdWO 4 /Bi 2 WO 6 , [45] TiO 2 /Bi 2 MoO 6 , [46] CuO/Bi 2 MoO 6 , [47] and bimetallic AuÀ Pd/g-C 3 N 4 [48] reported previously in the activitation of aromatic hydrocarbons CÀ H for the selective introduction of oxygen molecule.…”
Section: Photocatalytic Oxidation Of α-Pinenementioning
confidence: 68%
“…Regarding the PTC of VOCs, the WO 3 /Ag/GdCrO 3 presents a remarkably higher toluene degradation rate of 0.22 min –1 , which is ∼73 times higher than that of the Type III heterojunction WO 3 /GdCrO 3 , Ag/WO 3 , and Ag/GdCrO 3 with an initial ∼700 ppm toluene concentration and visible-light irradiation at 363 K and 6 times higher than the sum of the photocatalytic oxidation of toluene without heating and thermocatalytic oxidation of toluene at 363 K without irradiation (Figure a, b and Figure S11), as well as faster than the recently reported Type B heterojunction Ag 3 PO 4 /Ag/GdCrO 3 (0.16 min –1 ) and the other recently reported catalysts for the photocatalytic or photothermocatalytic toluene degradation reaction (Figure b and Table S2). ,,, The WO 3 /Ag/GdCrO 3 also shows good cyclic stability for the photothermocatalytic toluene oxidation (Figure c) and excellent photothermocatalytic mineralization activity for benzene or xylene with the initial concentration of ∼700 ppm (Figure d). Thus, the introduction of Ag NP bridge into bandgap broken WO 3 /GdCrO 3 makes the as-developed Type B heterojunction WO 3 /Ag/GdCrO 3 a robust photothermocatalyst.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Comparison of apparent reaction rate constants ( k ) of WO 3 /Ag/GdCrO 3 with the recently reported materials (Table S2). ,,, (c) Cyclic stability of WO 3 /Ag/GdCrO 3 for toluene PTC. (d) Toluene, benzene, and xylene conversions versus time curves of WO 3 /Ag/GdCrO 3 under PTC conditions.…”
Section: Resultsmentioning
confidence: 99%